Spatial variation in water supply and demand across river basins of India - Amarasinghe, Upali A.; Sharma, Bharat R.; Aloysius, Noel; Scott, Christopher A.; Smakhtin, Vladimir U.; Fraiture, Charlotte de (International Water Management Institute, 2004)
India is a large country with regional differences in per-capita water supply and demand. Attempts to describe the water situation in India at a national level are often misleading due to the tremendous diversity in the water situation across the country. This Report analyzes the spatial variation of water supply and demand across river basins in India. The study identifies basins that are water-scarce because of inadequate water availability to meet the effective demand. It also identifies issues that are important for estimating the future water demand and for the formation of policy for future water-resources development and management.